Fruit Characterization of Prunus serotina subsp. capuli - Sakshi Pathania; Rachel A. Itle; Carlos R. Chávez; Luis F. Lema; Veronica Caballero-Serrano; Juan C. Carrasco; Dario J. Chavez (Horticulturae, 2022)
Prunus serotina is divided into five subspecies. Among these, P. serotina subsp. capuli, commonly known as capuli, is native to Central and South America. Its fruits are big, sweet, and consumed by locals in various forms, with the Ecuadorian Andes region providing the best fruit forms of capuli. The objective of this study was to characterize a collection of different genotypes of capuli’s fruit, and their endocarps, found growing in the wild in the Chimborazo, Tungurahua, and Cotopaxi provinces of Ecuador. The fruits were characterized for weight (11.7–50.3 g), diameter (12.4–21.7 mm), height (11.4–19.7 mm), and soluble solids content (SSC) (13.4–27.6 °Brix) across two years. Similarly, the endocarps’ diameters (7.5–12.2 mm) and heights (8.1–13.6 mm) were measured. Significant differences were found for all the fruit and endocarp variables studied. A multivariate analysis showed that all the fruit and endocarp size characteristics, except SSC, were positively correlated with each other within a season. No clear population differentiation was seen among the genotypes from different provinces, suggesting a lack of clear morphological differentiation. The future breeding and selection of a capuli with superior, commercial, large fruit and a high SSC shows great potential.